Penerapan Pembelajaran Diferensiasi Dalam Meningkatkan Hasil Belajar Siswa - Sijabat, Dermawati (JURNAL GLOBAL EDUKASI, 2022)
Abstract: This study aims to improve student learning outcomes in science subjects on the subject of Substances and their Changes. This research uses differentiated learning by involving three elements, namely visual, auditory, and kinesthetic. This research is a class action research which is divided into two cycles and begins with a pre-cycle. Each cycle consists of planning, action implementation, observation, evaluation, and reflection. As for the results of research conducted on 35 students, in pre-cycle activities the number of students who were complete was 12 students (34.28%), while students who were not complete were 23 students (65.72%), with an average score of 55.14. In cycle I students experienced an increase in the number of students who completed 20 students (57.14%) while the number of students who had not completed was 15 students (42.85%) with an average score of 70. Then in cycle II, there was a very high increase compared to the previous cycle, namely students who had reached the KKM were 32 students (91.42%), while students who had not completed were 3 students (8.57%) with an average score of 78.85.Keywords: differentiated learning; learning outcomesAbstak: Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada mata pelajaran IPA pokok bahasan Zat dan Perubahannya. Penelitian ini menggunakan pembelajaran berdiferensiasi dengan melibatkan tiga unsur yaitu visual, auditori, dan kinestetik. Penelitian ini merupakan penelitian tindakan kelas yang dibagi menjadi dua siklus dan di awali dengan prasiklus. Setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, obeservasi, evaluasi, dan refleksi. Adapun hasil penelitian yang dilaksanakan pada 35 orang siswa, pada kegiatan pra siklus jumlah siswa yang tuntas adalah 12 siswa (34,28 %), sedangkan siswa yang belum tuntas 23 siswa (65,72 %), dengan nilai rata-rata 55,14. Pada siklus I siswa mengalami peningkatan jumlah siswa yang tuntas 20 siswa (57,14%) sedangkan siswa yang belum tuntas berjumlah 15 siswa (42,85%) dengan nilai rata-rata 70 . Kemudian pada siklus II ini mengalami peningkatan yang sangat tinggi dibandingkan dengan siklus sebelumnya yaitu siswa yang sudah mencapai KKM berjumlah 32 siswa (91,42 %), sedangkan siswa yang belum tuntas berjumlah 3 siswa (8,57 %) dengan nilai rata-rata 78,85.Kata kunci: pembelajaran berdiferensiasi; hasil belajar